2009
DOI: 10.1093/brain/awp217
|View full text |Cite
|
Sign up to set email alerts
|

Functional definition of seizure provides new insight into post-traumatic epileptogenesis

Abstract: Experimental animals’ seizures are often defined arbitrarily based on duration, which may lead to misjudgement of the syndrome and failure to develop a cure. We employed a functional definition of seizures based on the clinical practice of observing epileptiform electrocorticography and simultaneous ictal behaviour, and examined post-traumatic epilepsy induced in rats by rostral parasagittal fluid percussion injury and epilepsy patients evaluated with invasive monitoring. We showed previously that rostral para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 25 publications
9
88
0
Order By: Relevance
“…Although the occipital and temporal IRDA are more commonly associated with seizures than the frontal IRDA, 38 they are not etiologically specific and are relatively less common in TBI and stroke patients. Recently, D'Ambrosio et al 39 described an electrocorticography (ECoG) phenomenon in a rat lateral FP injury model, which seemed to be very similar to the IRDA observed in this study in the PBBI and pMCAO models. In their study the brief (*2 sec) bursts of delta or theta spike oscillations were referred to as ''epiletiform electrocorticography events (EEE),'' and were considered as true post-traumatic ictal activities because of the concomitant behavioral components during each event.…”
Section: Other Epileptic Activitiessupporting
confidence: 86%
“…Although the occipital and temporal IRDA are more commonly associated with seizures than the frontal IRDA, 38 they are not etiologically specific and are relatively less common in TBI and stroke patients. Recently, D'Ambrosio et al 39 described an electrocorticography (ECoG) phenomenon in a rat lateral FP injury model, which seemed to be very similar to the IRDA observed in this study in the PBBI and pMCAO models. In their study the brief (*2 sec) bursts of delta or theta spike oscillations were referred to as ''epiletiform electrocorticography events (EEE),'' and were considered as true post-traumatic ictal activities because of the concomitant behavioral components during each event.…”
Section: Other Epileptic Activitiessupporting
confidence: 86%
“…However, since we did not perform electrophysiological measurements, we cannot rule out the possibility that sham-operated animals had subclinical epileptic activity that was not detected behaviorally. Previous studies have correlated these clinical measures of seizure activity to abnormal electrophysiological recordings taken from both cortical and subcortical areas (D'Ambrosio et al, 2004;D'Ambrosio et al, 2009;Hunt et al, 2009Hunt et al, , 2010Kharatishvili et al, 2006;Kharatishvili and Pitkanen, 2010). These studies emphasize that in the clinical situation, periods of PTE could have profound effects on the natural history of the injury process and the long-term consequences of the primary insult (Vespa et al, 2010).…”
Section: Post-traumatic Seizures Exacerbate Damagementioning
confidence: 96%
“…Clinical studies have demonstrated that spontaneous episodes of PTE occur at variable time periods after TBI and are considered an important second injury mechanism after trauma. In experimental studies, researchers have also reported spontaneous episodes of PTE most commonly after severe TBI in rodent models (Coulter et al, 1996;D'Ambrosio et al, 2004;D'Ambrosio et al, 2009;Hunt et al, 2009Hunt et al, , 2010Kharatishvili et al, 2006;Kharatishvili and Pitkanen, 2010;Lowenstein et al, 1992;Nilsson et al, 1994;Santhakumar et al, 2001). In these studies, PTE is commonly recorded in a subpopulation of rats with injury strategies leading to high mortality.…”
Section: Post-traumatic Seizures Exacerbate Damagementioning
confidence: 99%
See 1 more Smart Citation
“…This is an etiologically realistic syndrome specific PTE model based on an experimental brain insult, FPI, that has long been regarded as a realistic model of contusive closed head injury in man (Thompson et al., 2005). We have previously optimized this model with respect to the location and severity of injury to produce rapid and reliable epileptogenesis with low acute mortality (Curia et al, 2011, in press; D’Ambrosio et al, 2009), and have identified the location of the early epileptic focus that develops after injury. This has been mapped with grid and depth electrode recordings (D’Ambrosio et al, 2005, 2009), as well as by focal cooling of the perilesional neocortex (D’Ambrosio et al, 2013).…”
Section: Introductionmentioning
confidence: 99%